History, Literature, and Music in Scotland, 700-1560 - McDonald, R. Andrew (Russell Andrew), 1965- (Book collections on Project MUSE., 2002)
McDonald brings together contributions from scholars working in different disciplines but with a common interest in this history and society of Scotland between AD 700 and AD 1560.